Effective delegation enables managers to have more time for their priority activities Case Study: Financial businesses and insurance activities in Kosovo - Trakaniqi, Fjolla (Technium Social Sciences Journal, 2020)
Abstract. Time management is a primary issue in managers’ job. The implementation of the advantages enables the manager to neglect all those tasks that hinder the fulfilment of more important tasks that can be done by others or should be left for later. The main role in the continuity of the work process has the manager, who manages the entire process. Delegation of tasks is one of the essential skills of effective management, which is becoming more and more a priority of managerial staffs. One key element of the manager is to find the right people for the right tasks. Successful managers are those who can get the best performance from subordinates. To achieve this, besides the information, knowledge and tools which they give to subordinates, they must also motivate them. At the same time, effective delegation requires that the authority for the use of resources be equal to the responsibility given to delegates. The purpose of this research is to identify how much effective delegation enables managers to have more time for priority activities. To achieve this, in the paper was discussed the process of delegating of 135 business managers in financial and insurance activity in Kosovo. In order to obtain the right information on the attitudes and the way of delegation from the managers of these businesses, was used a survey of 135 business managers. The results of this study proved H.1 hypothesis. Effective delegation enables managers to have more time for priority activities.